P006 Effects of Zonisamide on human motor cortical plasticity: A TMS study. Issue 3 (March 2017) - Shimizu, T.; Hanajima, R.; Tanaka, N.; Tsutsumi, R.; Shirota, Y.; Terao, Y.; Ugawa, Y.
Abstract : Introduction: Zonisamide (ZNS) was reported to be effective for patients with Parkinson's disease (PD). However, anti-Parkinsonian mechanisms of ZNS remain unclear. Some reports suggest that abnormal cortical plasticity is related to pathophysiology of PD. Previous study revealed that Levodopa, which is a crucial drug for PD treatment, enhances plasticity-like effects induced by rTMS in normal subjects, or restores LTP-like effects in PD patients. Objectives: We studied the influence of ZNS on the motor cortical LTP-like effect induced by Quadripulse Transcranial Magnetic Stimulation (QPS) in normal subjects. Materials and methods: 24 healthy volunteers (12 men and 12 women; 65.8 ± 2.4 years old) participated in this study. The study design was a double-blinded, complete crossover and placebo-controlled form. The subject took either ZNS (25 mg) or a placebo in each session. Two hours after a capsule intake, QPS was given over the left M1 after measuring the motor thresholds (RMT/AMT) and the baseline MEP size. QPS consists of bursts of four monophasic TMS pulses separated by inter-stimulus intervals of 5 ms, which is the best interval for LTP induction, and was repeated every 5 s for 30 min. We measured the MEP amplitude at 0, 5, 10, 15, 20, and 25 min after the end of the QPS. We divided the subjects into "responders" and "non-responders" according to a previously reported definition and compared the time courses between the experimental conditions in each group of subjects separately. Results: 14 participants were defined as a responder, and the other 10 were as a non-responder. There were no significant differences in the RMT, AMT, baseline MEP, or the single pulse TMS intensity that was used between responders and non-responders. ZNS significantly enhanced the LTP in non-responders ( p  = 0.008), but not in responders ( p  = 0.48). Conclusion: ZNS significantly enhanced LTP in non-responders, but had no influence in responders. The mild LTP enhancement by ZNS shown here may partly explain its anti-Parkinsonian mechanisms.